Organisasi Cacat Pejuang Kemerdekaan Indonesia: Dari Ikatan Invaliden Indonesia Hingga Korps Cacad Veteran (1946-1983) - Rinie Cahaya Hati; Nur’aeni Marta; Sri Martini (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2021)
The Indonesian War of Independence that occurred in the period 1946-1949 caused many war victims to become disabled. This research will discusses how the next struggle of the soldiers who became disabled as a result of the war of Indonesian Independence (1946-1983). This study aims to describe the formation and development of disabled organizations for Indonesian independence fighters in their efforts to continue to be useful to the country and to improve the lives of their members in the period 1946-1983. This study uses historical research methods with the stages of heuristic research, criticism, interpretation and historiography. The results of this study indicate that the establishment of a disabled organization for freedom fighters in 1946 in Malang under the name of the Indonesian Invaliden Association was motivated by efforts to empower and prosper the disabled victims of the war of independence and in its development until 1983 showed that this organization contributed to its members, namely getting welfare and providing opportunities for continue to be useful to the country.